Accept your baptism, and die!: Redemption, Death and Baptism in Bioshock Infinite - Bosman, Frank (Gamevironments, 2017)
In 2013, self-described Christian and devout believer' Breen Malmberg requested and received a refund for the game Bioshock Infinite (2013) from Valve, on the basis of his objections to an unskippable scene in the game. In the offending scene, which occurs early in the game, the game forces the protagonist, Booker DeWitt, to undergo a Christian baptismal ritual. The ritual is mandatory for the player in order to proceed with the game. Malmberg characterized the choice as extreme blasphemy'. When the player decides to undergo the ritual, he is (almost) drowned in the process. That at least four of these baptismal' rituals, all with lethal consequences, occur in Bioshock Infinite, a game whose narrative context is critical of the religiously inspired exceptionalism of the United States of America, is highly interesting. Developer Irrational Games has succeeded not only in incorporating religious beliefs, rituals and criticisms in a highly-complex narrative, but also in inviting (or even: forcing) the player to participate in ritual behavior itself.